Academic Underachievement: A Reformulation and Rectification - Sharma, Lal (Canadian Journal of Counselling and Psychotherapy, 1972)
With the increasing importance that our society is placing on education, the problem of underachievement in schools has come to take on considerable social significance. Numerous attempts have been made to rectify the kind of irrational factors which help prevent a young person from meeting one of society's first demands - that of satisfactory school performance. This paper discusses some of the existing literature on the subject, especially a rather effective technique suggested by Ellis.